2008
DOI: 10.1104/pp.108.122457
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Lineage-Specific Expansion of Plant Tandem Duplicates in the Adaptive Response to Environmental Stimuli  

Abstract: Plants have substantially higher gene duplication rates compared with most other eukaryotes. These plant gene duplicates are mostly derived from whole genome and/or tandem duplications. Earlier studies have shown that a large number of duplicate genes are retained over a long evolutionary time, and there is a clear functional bias in retention. However, the influence of duplication mechanism, particularly tandem duplication, on duplicate retention has not been thoroughly investigated. We have defined orthologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
402
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(454 citation statements)
references
References 60 publications
31
402
0
2
Order By: Relevance
“…Adaptations possibly related to the arborescent habit were visible in convergent tandem expansions shared by B. pendula and Populus trichocarpa, including genes associated with fungal pathogen defense, cell wall biogenesis, and cellulose synthase activity (Supplementary Tables 11 and 12). Through evolutionary information stored within single genomes, these results suggest that whereas polyploid duplicates tend to diversify core processes in developmental and physiological regulation, tandem duplicates enhance the diversity of a plant's environmental response capacity, which is in concurrence with previous studies 15,17,18 .…”
supporting
confidence: 88%
“…Adaptations possibly related to the arborescent habit were visible in convergent tandem expansions shared by B. pendula and Populus trichocarpa, including genes associated with fungal pathogen defense, cell wall biogenesis, and cellulose synthase activity (Supplementary Tables 11 and 12). Through evolutionary information stored within single genomes, these results suggest that whereas polyploid duplicates tend to diversify core processes in developmental and physiological regulation, tandem duplicates enhance the diversity of a plant's environmental response capacity, which is in concurrence with previous studies 15,17,18 .…”
supporting
confidence: 88%
“…5) and conserved gene order on independent BAC clones spanning two large tandem gene arrays (Supplementary Data 3 and Supplementary Information 1) support the accuracy of the assembly across highly similar tandem copies. Tandem duplication often involves stress-response genes that are retained in a lineage-specific fashion, suggesting that tandem duplication is important for adaptive evolution in dynamically changing environments 16 . For example, more than 80% of the S-domain receptorlike kinase (SDRLK) subfamily occurs in tandem arrays (Supplementary Data 4).…”
Section: Research Articlementioning
confidence: 99%
“…As the result of unequal crossing-over during recombination, tandem duplications vary in their 'genetic neighborhoods', with copies receiving different regulatory motifs that can lead to drastic changes in expression [40]. A comparative study on plant genomes ranging from Arabidopsis to Physcomitrella showed genes associated with defense, transport functions, or abiotic stress responses enriched in tandem duplicates, whereas duplicates due to other mechanisms included genes enriched in other intracellular regulatory roles [41]. …”
Section: Stress Adaptation By Gene Duplicationmentioning
confidence: 99%